Modifying Enzymes Are Elicited by ER Stress, Generating Epitopes That Are Selectively Recognized by CD4+ T Cells in Patients With Type 1 Diabetes - Marre, Meghan L.; McGinty, John W.; Chow, I-Ting; DeNicola, Megan E.; Beck, Noah W.; Kent, Sally C.; Powers, Alvin C.; Bottino, Rita; Harlan, David M.; Greenbaum, Carla J.; Kwok, William W.; Piganelli, Jon D.; et al. (Diabetes (New York, N.Y.), 2018)
In spite of tolerance mechanisms, some individuals develop T-cell–mediated autoimmunity. Posttranslational modifications that increase the affinity of epitope presentation and/or recognition represent one means through which self-tolerance mechanisms can be circumvented. We investigated T-cell recognition of peptides that correspond to modified β-cell antigens in subjects with type 1 diabetes. Modified peptides elicited enhanced proliferation by autoreactive T-cell clones. Endoplasmic reticulum (ER) stress in insulinoma cells increased cytosolic calcium and the activity of tissue transglutaminase 2 (tTG2). Furthermore, stressed human islets and insulinomas elicited effector responses from T cells specific for modified peptides, suggesting that ER stress–derived tTG2 activity generated deamidated neoepitopes that autoreactive T cells recognized. Patients with type 1 diabetes had large numbers of T cells specific for these epitopes in their peripheral blood. T cells with these specificities were also isolated from the pancreatic draining lymph nodes of cadaveric donors with established diabetes. Together, these results suggest that self-antigens are enzymatically modified in β-cells during ER stress, giving rise to modified epitopes that could serve to initiate autoimmunity or to further broaden the antigenic repertoire, activating potentially pathogenic CD4+ T cells that may not be effectively eliminated by negative selection.